(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
Electrospray coating is a method of generating fine droplets of polymer through high electrostatic charging. It involves electrohydrodynamic process for forming fine polymer droplets. These droplets are highly charged that promotes self-dispersion which results in uniform coating on substrate. Electrospray coating can be successfully utilised as a coating technique to coat textile substrates. Textiles substrate coated with electrosprayed polymer droplets have a large specific surface area and it facilitates submicron range coating compared to conventional coating methods like roller coating or knife coating. This research study investigates the electrospray coating of thermoplastic polyurethane polymer on textile substrate. The results showed that electrospraying facilitated the submicron size droplets deposition on textile substrates which imparted the waterproof property to the substrate without altering the moisture management and surface properties of textile substrate.